On the Generation and Salinity Impacts of Intraseasonal Westward Jets in the Equatorial Indian Ocean. Issue 6 (15th June 2020) - Nyadjro, Ebenezer S.; Rydbeck, Adam V.; Jensen, Tommy G.; Richman, James G.; Shriver, Jay F.
Abstract: While westerly winds dominate the equatorial Indian Ocean and generate the well‐known eastward flowing Wyrtki Jets during boreal spring and fall, there is evidence of a strong westward surface jet during winter that is swifter than eastward currents during that season. A weaker westward jet is found in summer. In this study, we report the occurrence, characteristics, and intraseasonal variability of this westward jet and its impact on mixed layer salinity in the equatorial Indian Ocean using the HYbrid Coordinate Ocean Model (HYCOM) reanalysis with the Navy Coupled Ocean Data Assimilation (NCODA). The westward jet typically occurs in the upper 50 m, above an eastward flowing equatorial undercurrent, with peak westward volume transport of approximately −8 Sv. The westward jet builds up gradually, decays rapidly, and is primarily forced by local intraseasonal wind stress anomalies generated by atmospheric intraseasonal convection. Westward acceleration of the jet occurs when the dominant intraseasonal westward wind anomaly is not balanced by the zonal pressure gradient (ZPG) force. The intraseasonal westward jet generates strong horizontal advection and is the leading cause of mixed layer freshening in the western equatorial Indian Ocean. Without it, a saltier mixed layer would persist and weaken any barrier layers. Existing barrier layers are strengthened following the passage of freshwater‐laden westward jets. Deceleration of the westward jet occurs when the eastward ZPG becomes increasingly important and the westward intraseasonal wind anomalies weaken. A rapid reversal of atmospheric intraseasonal convection‐driven surface winds eventually terminates the westward jet. Plain Language Summary: This study investigates currents that flow and travel from east to west along the equator in the Indian Ocean. We examine potential mechanisms of current variability using a reanalysis version of the global HYbrid Coordinate Ocean Model (HYCOM). The Indian Ocean experiences seasonal wind reversals, which drive much of the surface ocean dynamics. Our results show that the winds vary more frequently than the currents. These intraseasonal winds are the main causes of intense westward currents. The westward jet is stronger during winter than summer, a likely result of winds persisting for a longer time during winter than during summer. Strong intraseasonal westward currents transport freshwater from the east to the central and western Indian Ocean. Rapid reversal of the intraseasonal winds from westward to eastward causes the surface currents to reverse direction from westward to eastward. Key Points: Intraseasonal equatorial westward jet anomalies in the Indian Ocean are generated and terminated by local intraseasonal surface winds Barrier layer thickness increases following the passage of westward jets Intraseasonal westward jets freshen the equatorial mixed layer through zonal advection